2016
DOI: 10.1016/j.bpj.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Signaling in MIN6 β -Cells Revealed by Fluorescence Fluctuation Spectroscopy

Abstract: Insulin secretion defects are central to the development of type II diabetes mellitus. Glucose stimulation of insulin secretion has been extensively studied, but its regulation by other stimuli such as incretins and neurotransmitters is not as well understood. We investigated the mechanisms underlying the inhibition of insulin secretion by dopamine, which is synthesized in pancreatic β-cells from circulating L-dopa. Previous research has shown that this inhibition is mediated primarily by activation of the dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…These cells are being widely used for preliminary investigations on beta‐cell biology and drug targets. For example, recent investigations include exploration of dopamine receptor signalling, lipidomic profiling, antidiabetic actions of dogfish glucagon analogues, high‐throughput screening for inhibitors of beta‐cell apoptosis, Ca 2+ channel clustering with insulin granules in diabetes, mitochondrial dynamics and bioenergetics as well as involvement of neuronal K + Cl − cotransporter in insulin secretion . These investigations lay a foundation for further studies on understanding of beta‐cell biology in health and disease.…”
Section: Development and Experimental Use Of Rodent Beta‐cell Linesmentioning
confidence: 99%
“…These cells are being widely used for preliminary investigations on beta‐cell biology and drug targets. For example, recent investigations include exploration of dopamine receptor signalling, lipidomic profiling, antidiabetic actions of dogfish glucagon analogues, high‐throughput screening for inhibitors of beta‐cell apoptosis, Ca 2+ channel clustering with insulin granules in diabetes, mitochondrial dynamics and bioenergetics as well as involvement of neuronal K + Cl − cotransporter in insulin secretion . These investigations lay a foundation for further studies on understanding of beta‐cell biology in health and disease.…”
Section: Development and Experimental Use Of Rodent Beta‐cell Linesmentioning
confidence: 99%
“…Clinical studies have reported that patients with Parkinson's disease who were treated with the long-term dopamine precursor L-dopa had a significant reduction in glucose tolerance and even developed type 2 diabetes (9). In recent years, dopamine has been proposed to be important in regulating glucose-stimulated insulin secretion (10,11). However, the characteristic effect of dopamine on insulin secretion and the underlying electrophysiological mechanism have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of pmApple-GNG2 was described previously (17). pEGFP-DRD2 was obtained from Jean-Michel Arrang via Addgene (#24099) (18).…”
Section: Plasmidsmentioning
confidence: 99%